2003
DOI: 10.1114/1.1555626
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effect on a Viscously Deformed Liposome in a Laser Trap

Abstract: The viscous drag and mechanical deformation of a single vesicle under hydrodynamics flow during the phase transition of a lipid bilayer is determined by optical tweezers experiments with the aid of computational fluid dynamics simulations. Based on the experimental geometry of the vesicle under hydrodynamics flow, the surface stresses and drag force are numerically calculated. It is found that the vesicle is less rigid and the viscous drag force of the vesicle decreases with the increase of temperature at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Based on the images, the total projected area of the vesicles slightly increases with the increase of hydrodynamic flow velocity, which is identical to the far‐field flow velocity in a Lagrangian coordinate as fully described in classic fluid mechanics literature (Batchelor, 1967). A similar result has been reported in the deformation of phospholipid vesicle under a change of laser power within the optical trap (Foo et al, 2003). Although four DDPC vesicles of different sizes, that is, ULV1 and ULV 3‐5 (their experimental and calculated data will be reported in Figure 4 and 5), only one set of the images is shown in Figure 2 for simplicity.…”
Section: Resultssupporting
confidence: 87%
“…Based on the images, the total projected area of the vesicles slightly increases with the increase of hydrodynamic flow velocity, which is identical to the far‐field flow velocity in a Lagrangian coordinate as fully described in classic fluid mechanics literature (Batchelor, 1967). A similar result has been reported in the deformation of phospholipid vesicle under a change of laser power within the optical trap (Foo et al, 2003). Although four DDPC vesicles of different sizes, that is, ULV1 and ULV 3‐5 (their experimental and calculated data will be reported in Figure 4 and 5), only one set of the images is shown in Figure 2 for simplicity.…”
Section: Resultssupporting
confidence: 87%
“…The sample was equilibrated at the prescribed temperature for at least 10 min before the sudden-stop experiment was started. A series of images within the first 5 s immediately following the sudden stop of liposome were captured with the CCD camera (a similar image analysis method can be found in [16], [20]). The time interval of every image taken is set at 0.25 s, as it has been observed that after the hydrodynamic/blocked motion, a vesicle required more time in shape recovery.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, optical tweezers has emerged as a novel tool for manipulating cells, vesicles, and other supramolecular structures and for performing sophisticated biophysical characterizations. Foo et al has recently applied optical tweezers to study the flow-induced vesicles deformation during the main phase transition of phospholipid bilayer [16]. In the previous study, a single liposome trapped inside an optical trap is pulled at a constant velocity and temperature and its degree of deformation under low Reynolds number flow is simultaneously probed by a charge-coupled device (CCD) camera-enhanced microscope system.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas sometimes laser induced-heating is desirable, such as in photothermal therapy of cancer tumors 14 , in trapping experiments temperature increments will be detrimental in most cases, leading to undesired changes in the properties of the studied systems. Moreover, when working with biological samples, even temperature increments below 5º C will cause alterations in the biochemistry and molecular machinery of cells 15,16 . If temperature reaches the cytotoxic level (43º C), cell death will be triggered through apoptosis or necrosis 17,18 .…”
Section: Introductionmentioning
confidence: 99%